Stereoselective Glycosylations by Nitrosyl Tetrafluoroborate-Catalyzed Activation of Glycosyl Trichloroacetimidate Derivatives - Sau, Abhijit; Santra, Abhishek; Misra, Anup Kumar (Synlett, 2012)
Efficient stereoselective glycosylation conditions have been developed by using nitrosyl tetrafluoroborate (NOBF4) promoted activation of glycosyl trichloroacetimidate derivatives. A series of mono- and disaccharide derivatives were synthesized in excellent yield, and high stereoselectivity at the glycosylation center was observed in every case.
Keywords: glycosylation; glycosides; stereoselective synthesis; oligosaccharides; carbohydrates